A study on the infection rate of coccidia and distribution of coccidiosis of village chickens in South and East Kalimantan - ., Salfina; Hamdan, A.; Partoutomo, S. (Indonesian Animal Sciences Society, 1995)
The infection rate of coccidia and distribution of coccidiosis of village chickens were studied in South Kalimantan (the districts of Hulu Sungai Tengah, Hulu Sungai Selatan, Tanah Laut, and Tapin) and East Kalimantan (the districts of Pasir) . Six hundred and thirty one fecal and intestinal content of clinically infected young and adult birds were sampled, and microscopically and morphologically examined againts the Eimetia species . The result indicated that the average infection rate was 39 .3% where 40 .7% for young and 38 .5% for adult birds with an opg (oocyst per gram) ranging from 40 to 8,200 . Seven species of Eimetia were identified, i .e . E. tenella 23 .6%, E. maxima 13 .6%, E. necattix 11 .3%, E. acervtdina 6 .7%, E. mitis 3 .6%, E. mivati 2.2%, and E. brvnetti 0 .8% . Infection rate of E. tenella was the highest either in South Kalimantan or in East Kalimantan than the other species, while E. brttnetti was the lowest . Key words : Village chicken, infection rate, coccidiosis